Functionele aspecten van de gecomputeriseerde lexicografie - Kist, Joost (Lexikos, 1999)
Functional Aspects of Computerised LexicographyThe computerisation of lexicography has meant that traditional dictionaries are now supported, supplemented and — in some places — already supplanted by new electronic off- and online information carriers. The Woordenboek der Nederlandsche Taal (WNT) which was "completed" in 1998 and its electronic successors form a case study of these developments. In addition to a short description of the WNT project, this article also focuses on the functional aspects of computerised lexicography. Some of the more general aspects of information and knowledge technology are stressed, including the role of the user who needs to carry out his/her searches through the language banks of the future with the least possible effort.